Rancang Bangun Alat Peraga Sistem Pneumatik dan Pengujian Dua Silinder Kerja Ganda Bergerak Bersamaan Secara Terus-Menerus - Ari Kurniawan; Hilda Porawati; Siti Aminah (LPPM Politeknik Jambi, 2021)
Teaching aids are tools used to teach and help explain the material. The teaching aids that the author makes are pneumatic system props and testing of two double acting cylinders moving simultaneously continuously. This teaching aid is made through the design stage. This teaching aid was made to serve as a learning practicum tool in the Jambi Polytechnic workshop and to conduct testing. In the final project report, the author made a pneumatic system that has the actuator motion automatically. Thus the components used to make the actuator move automatically, namely 4 manifold ports, 1 3/2 pushbutton valve, 2 3/2 roller valves, 1 5/2 double pilot valve where the air flow will be branched using a T fitting to each each cylinder, namely cylinder 1 and cylinder 2. This teaching aid has a length of 80 cm, a width of 80 cm and a height of 150 cm. All pneumatic components are mounted on pneumatic sliding boards by connecting them with pneumatic rails.